Practical considerations for implementing genomic information resources - Rasmussen, Luke V.; Overby, Casey L.; Connolly, John; Chute, Christopher G.; Denny, Joshua C.; Freimuth, Robert R.; Hartzler, Andrea L.; Holm, Ingrid A.; Manzi, Shannon; Pathak, Jyotishman; Peissig, Peggy L.; Smith, Maureen; Williams, Marc S.; Shirts, Brian H.; Stoffel, Elena M.; Tarczy-Hornoch, Peter; Vitek, Carolyn R. Rohrer; Wolf, Wendy A.; Starren, Justin (Applied Clinical Informatics, 2016)
To understand opinions and perceptions on the state of information resources specifically targeted to genomics, and approaches to delivery in clinical practice.We conducted a survey of genomic content use and its clinical delivery from representatives across eight institutions in the electronic Medical Records and Genomics (eMERGE) network and two institutions in the Clinical Sequencing Exploratory Research (CSER) consortium in 2014.Eleven responses representing distinct projects across ten sites showed heterogeneity in how content is being delivered, with provider-facing content primarily delivered via the electronic health record (EHR) (n=10), and paper/pamphlets as the leading mode for patient-facing content (n=9). There was general agreement (91%) that new content is needed for patients and providers specific to genomics, and that while aspects of this content could be shared across institutions there remain site-specific needs (73% in agreement).This work identifies a need for the improved access to and expansion of information resources to support genomic medicine, and opportunities for content developers and EHR vendors to partner with institutions to develop needed resources, and streamline their use – such as a central content site in multiple modalities while implementing approaches to allow for site-specific customization.Citation: Rasmussen LV, Overby CL, Connolly J, Chute CG, Denny JC, Freimuth RR, Hartzler AL, Holm IA, Manzi S, Pathak J, Peissig PL, Smith M, Williams MS, Shirts BH, Stoffel EM, Tarczy-Hornoch P, Rohrer Vitek CR, Wolf WA, Starren J. Practical considerations for implementing genomic information resources – experiences from eMERGE and CSER.
Keywords: Electronic health records; genetics; clinical decision support; medicine; education